2022
DOI: 10.3390/biomedicines10112709
|View full text |Cite
|
Sign up to set email alerts
|

Self-Renewal of Macrophages: Tumor-Released Factors and Signaling Pathways

Abstract: Macrophages are the most abundant immune cells of the tumor microenvironment (TME) and have multiple important functions in cancer. During tumor growth, both tissue-resident macrophages and newly recruited monocyte-derived macrophages can give rise to tumor-associated macrophages (TAMs), which have been associated with poor prognosis in most cancers. Compelling evidence indicate that the high degree of plasticity of macrophages and their ability to self-renew majorly impact tumor progression and resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 176 publications
0
3
0
Order By: Relevance
“…Moreover, c-Maf controls the inhibitory activity of TAMs because it is strongly upregulated in these cells. 222 Research from Liu et al 221 confirmed that tumor load is decreased alongside improved anticancer T cell immunity after selective elimination of c-Maf in myeloid cells. The researchers also found that in a model of subcutaneous LLC tumors, blocking c-Maf partially removes resistance to anti-PD-1 treatment.…”
Section: Ifn Regulatory Factorsmentioning
confidence: 97%
“…Moreover, c-Maf controls the inhibitory activity of TAMs because it is strongly upregulated in these cells. 222 Research from Liu et al 221 confirmed that tumor load is decreased alongside improved anticancer T cell immunity after selective elimination of c-Maf in myeloid cells. The researchers also found that in a model of subcutaneous LLC tumors, blocking c-Maf partially removes resistance to anti-PD-1 treatment.…”
Section: Ifn Regulatory Factorsmentioning
confidence: 97%
“…Macrophages and macrophage-like cells, such as dendritic cells, microglia, and osteoclasts, also rely on vesicular trafficking for fighting infections, general housekeeping functions and for tumors. A 2A R-mediated signaling plays an important role in the self-renewal of macrophages in the tumor microenvironment [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The communication between the tumor, stromal and immune cells in the tumor microenvironment (TME) is necessary for the establishment of an environment that is suitable for tumor cell growth [33], proliferation and invasion of secondary tissues [34]. In this scenario, CSF-1R ligands, IL-34 and M-CSF, play an important role in the crosstalk between immune and tumor cells, as, in fact, immune and cancer cells secreted cytokines and interleukins, which supported tumor development and progression [33,35]. In colorectal cancer (CRC), cancer cells secrete IL-34 and express CSF-1R, suggesting the presence of an autocrine positive feedback loop on the receptor.…”
Section: Role Of Csf-1r Ligands In Tme Crosstalkmentioning
confidence: 99%